Investment Proximity and Venture Capital Returns - Krishnan, CNV; Nguyen, Daniel (Journal of Accounting and Finance, 2021)
Using a large dataset of 82,818 investments in start-up firms from December 1965 through August 2019, we document that the biggest group of investors are venture capital firms (about 79% of all observations). The majority of in-state investments are found clustered in California (with the San Francisco VC Hub), Massachusetts (with the Boston VC Hub) and New York. Early round investors get a higher return than late stage investors, and IPO exits entail the highest return. We find that geographical proximity is significantly and positively associated with cumulative returns or annualized returns, when we use actual distance (in km) between the VC investment firm HQ and portfolio firm HQ, or a cross-region indicator variable when the portfolio firm HQ is out-of-state as compared to VC investment firm HQ. The relation between investment proximity and returns continues to be robust even after controlling for selection bias, and in a matched-sample analysis where we pair each proximate investment with a matched distant investment. We find that VC Director and other outside directors as a proportion of all Directors on the boards on portfolio companies is significantly higher, on average, for in-state and shorter distance investments as compared to out-of-state and longer distance investments, indicating higher involvement of VCs in their more proximate investments.